Improving Entrepreneurial Competence Through Talent - suranto suranto; Bakhrizal Bakhrizal; Adcharina Pratiwi; Dwi Indah Oktaviani (JTI: Jurnal Teknik Industri, 2023)
The research aims to determine the differences in the entrepreneurial mentality of talented or untalented students in conducting entrepreneurial incubation activities. The research uses a sample of students who have entrepreneurial talent and students who do not have entrepreneurial talent as participants in entrepreneurial incubation. Participants obtain guidance, mentoring, strengthening potential and facilitation in accordance with their respective talents. Talent mapping and mentoring are conducted through incubation treatment of students as an experimental group who have talent and students as a control group who do not have entrepreneurial talent. Both groups are equally treated with entrepreneurial mentoring. Data collection through interviews, questionnaires, documentation, literature studies, observations and research analysis with quasi-experimental trials of experimental groups (KE) and control groups (KK) with pretest-posttest control group design. The final result of the data through the trend of business development carried out by entrepreneurial participants. The development of the entrepreneurial mentality of students who have talent is higher than entrepreneurs who do not have entrepreneurial talent, based on valid model testing, goodness of fit is able to improve the entrepreneurial mentality of talent-based students.